KEMAMPUAN MEMBACA TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 23 PEKANBARU - Kurnia, Tiara Paramita; Razak, Abdul; Hakim, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study is entitled the ability to read exposition text of class VIII students of Pekanbaru State Junior High School 23. This study aims to find out and describe the ability to read the exposition text of class VIII Pekanbaru State Middle School 23, to find out whether there is a difference in the ability to read the exposition text of class VIII students of SMP Negeri 23 Pekanbaru between classes. This type of research is descriptive-quantitative. The population of this study amounted to 120 people and sample 116. The data of this study were the results of student test answers in working on the test of the ability to read the exposition text of class VIII Pekanbaru State Junior High School 23. The test used is an objective test consisting of four alternative answers. Data were analyzed by quantitative descriptive method through t-test to analyze the level of ability to read the exposition text of class VIII Pekanbaru State Junior High School 23, a one-way ANOVA test to determine the difference in the ability to read the exposition text of class VIII SMP Negeri 23 Pekanbaru between classes. The results of this study were in the form of a test of the ability to read the exposition text of class VIII student SMP Negeri 23 Pekanbaru, which was classified as high with a score of 83%.Key Words: Ability, Reading, Exposition